Observing polarization patterns in the collective motion of nanomechanical arrays - Doster, Juliane; Shah, Tirth; Foesel, Thomas; Paulitschke, Philipp; Marquardt, Florian; Weig, Eva M. (Nature Communications, 2022)
In recent years, nanomechanics has evolved into a mature field, and it has now reached a stage which enables the fabrication and study of ever more elaborate devices. This has led to the emergence of arrays of coupled nanomechanical resonators as a promising field of research serving as model systems to study collective dynamical phenomena such as synchronization or topological transport. From a general point of view, the arrays investigated so far can be effectively treated as scalar fields on a lattice. Moving to a scenario where the vector character of the fields becomes important would unlock a whole host of conceptually interesting additional phenomena, including the physics of polarization patterns in wave fields and their associated topology. Here we introduce a new platform, a two-dimensional array of coupled nanomechanical pillar resonators, whose orthogonal vibration directions encode a mechanical polarization degree of freedom. We demonstrate direct optical imaging of the collective dynamics, enabling us to analyze the emerging polarization patterns, follow their evolution with drive frequency, and identify topological polarization singularities.
CRIS-Team Scopus Importer:2022-05-20

Perturbation theory of nearly spherical dielectric optical resonators - Gohsrich, Julius; Shah, Tirth; Aiello, Andrea (Physical Review A, 2021)
Dielectric spheres of various sizes may sustain electromagnetic whispering-gallery modes resonating at optical frequencies with very narrow linewidths. Arbitrary small deviations from the spherical shape typically shift and broaden such resonances. Our goal is to determine these shifted and broadened resonances. A boundary-condition perturbation theory for the acoustic vibrations of nearly circular membranes was developed by Rayleigh more than a century ago. We extend this theory to describe the electromagnetic excitations of nearly spherical dielectric cavities. This approach permits us to avoid dealing with decaying quasinormal modes. We explicitly find the frequencies and the linewidths of the optical resonances for arbitrarily deformed nearly spherical dielectric cavities, as power series expansions by a small parameter, up to and including second-order terms. We thoroughly discuss the physical conditions for the applicability of perturbation theory.
CRIS-Team WoS Importer:2021-09-03

Topological phonon transport in an optomechanical system - Ren, Hengjiang; Shah, Tirth; Pfeifer, Hannes; Brendel, Christian; Peano, Vittorio; Marquardt, Florian; Painter, Oskar (2021 Conference on Lasers and Electro-Optics, CLEO 2021 - Proceedings, 2021)
We report the observation of topological phonon transport within a multiscale optome-chanical crystal structure consisting of an array of over 800 cavity-optomechanical ele-ments. Using sensitive, spatially resolved optical read-out we detect thermal phonons in a 0.325-0.34 GHz band traveling along a topological edge channel, with substantial reduc-tion in backscattering. This represents an important step from the pioneering macroscopic mechanical systems work towards topological phononic systems at the nanoscale.
CRIS-Team Scopus Importer:2021-12-24

Topological phonon transport in an optomechanical system - Ren, Hengjiang; Shah, Tirth; Pfeifer, Hannes; Brendel, Christian; Peano, Vittorio; Marquardt, Florian; Painter, Oskar (Nature Communications, 2022)
Light is a powerful tool for controlling mechanical motion, as shown by numerous applications in the field of cavity optomechanics. Recently, small scale optomechanical circuits, connecting a few optical and mechanical modes, have been demonstrated in an ongoing push towards multi-mode on-chip optomechanical systems. An ambitious goal driving this trend is to produce topologically protected phonon transport. Once realized, this will unlock the full toolbox of optomechanics for investigations of topological phononics. Here, we report the realization of topological phonon transport in an optomechanical device. Our experiment is based on an innovative multiscale optomechanical crystal design and allows for site-resolved measurements in an array of more than 800 cavities. The sensitivity inherent in our optomechanical read-out allowed us to detect thermal fluctuations traveling along topological edge channels. This represents a major step forward in an ongoing effort to downscale mechanical topological systems.
CRIS-Team Scopus Importer:2022-09-16

Tunneling-induced fractal transmission in valley Hall waveguides - Shah, Tirth; Marquardt, Florian; Peano, Vittorio (Physical Review B, 2023)
The valley Hall effect provides a popular route to engineer robust waveguides for bosonic excitations such as photons and phonons. The almost complete absence of backscattering in many experiments has its theoretical underpinning in a smooth-envelope approximation that neglects large momentum transfer and is accurate only for small bulk band gaps and/or smooth domain walls. For larger bulk band gaps and hard domain walls, backscattering is expected to become significant. Here, we show that in this experimentally relevant regime, the reflection of a wave at a sharp corner becomes highly sensitive to the orientation of the outgoing waveguide relative to the underlying lattice. Enhanced backscattering can be understood as being triggered by resonant tunneling transitions in quasimomentum space. Tracking the resonant tunneling energies as a function of the waveguide orientation reveals a self-repeating fractal pattern that is also imprinted in the density of states and the backscattering rate at a sharp corner.
CRIS-Team Scopus Importer:2023-03-03

Tunneling in the Brillouin zone: Theory of backscattering in valley Hall edge channels - Shah, Tirth; Marquardt, Florian; Peano, Vittorio (Physical Review B, 2021)
A large set of recent experiments has been exploring topological transport in bosonic systems, e.g., of photons or phonons. In the vast majority, time-reversal symmetry is preserved, and band structures are engineered by a suitable choice of geometry to produce topologically nontrivial band gaps in the vicinity of high-symmetry points. However, this leaves open the possibility of large-quasimomentum backscattering, destroying the topological protection. Up to now, it has been unclear what precisely the conditions are where this effect can be sufficiently suppressed. In the present paper, we introduce a comprehensive semiclassical theory of tunneling transitions in momentum space, describing backscattering for one of the most important system classes, based on the valley Hall effect. We predict that even for a smooth domain wall, effective scattering centers develop at locations determined by both the local slope of the wall and the energy. Moreover, our theory provides a quantitative analysis of the exponential suppression of the overall reflection amplitude with increasing domainwall smoothness.
CRIS-Team WoS Importer:2022-01-14